Feasibility and Reliability of Physical Fitness Tests Among Colombian Preschool Children - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The aim of the study was to assess the feasibility and reliability of physical fitness field tests used in the “Fuprecol kids” study among Colombian preschool children aged 3-5 years. A total of 90 preschoolers aged 3-5 years participated in the study. Weight, height, waist circumference, cardiorespiratory fitness (CRF), musculoskeletal fitness (handgrip strength and standing broad jump), speed-agility (4 × 10 m shuttle run), and flexibility (sit and reach test) components were tested twice (two weeks apart). The feasibility of the tests (preschoolers able to complete the test) ranged from 96% in the CRF test to 100% in the musculoskeletal fitness, speed-agility, and flexibility tests. Overall, the %TEMs were 0.625% for the weight, 0.378% for the height, 1.035% for the body mass index, and 0.547 % for the waist circumference. In addition, all tests were substantial reliable, for CRF (in stages and laps, concordance correlation coefficient = 0.944 and 0.941, respectively) in both sexes and flexibility (concordance correlation coefficient = 0.949) in girls. There were no significant differences in fitness test-retest mean differences in the boys (P gt; 0.05), except in CRF (laps P = 0.017). In girls, there were differences in CRF (stages (P = 0.017) and laps (P= 0.013)), and flexibility (P = 0.002) variables. The results from this study indicate that the “Fuprecol kids” battery of tests, administered by physical education teachers, was reliable and feasible for measuring components of physical fitness in preschoolers in a school setting in Colombia. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.